Metal Detector With Beat Frequency Method - Nuryadin Adil (Journal Basic Science and Technology, 2022)
The bomb terror that occurred in various regions is very troubling, because it causes us to feel anxious when we go anywhere. Bombs which are usually made of metal must be detected by a device called a metal detector "Tanaan" which can detect the presence of metal either embedded in metal or covered in other materials other than metal such as in suitcases or bags. On this occasion a metal detector with using the "Beat Freauencv Oscillator" method. The metal detector with this method uses two oscillators, namely the search coil and the reference oscillator. Inside the search coil oscillator there is a sensor in the form of a coil of copper wire and email where the frequency of the search coil oscillator is in, will change when the sensor is on. a certain distance adjacent to the metal.While the reference oscillation, has. Is a stable frequency. When a signal with frequency. If the signal generated by the search coil oscillator is mixed (mixed) with the signal generated by the reference oscillator, a pure frequency and both frequencies will be produced which can be heard by humans. The resulting sound is like a tapping sound with a certain rhythm and is often known as a heat note.